Implementation of Disaster Safe Education Unit (SPAB) At Quwwatul Islam Yogyakarta Al-Qur’an Education Park (TPA) - Yumidiana Tya Nugraheni; Agus Firmansyah (Journal of Contemporary Islamic Education, 2023)
This research is one of the efforts to reduce disaster risk in educational institutions, especially Al-Qur'an Education Park (TPA). This research is a qualitative research with a case study type. Obtaining data is done by observation, documentation, and interviews. As for data analysis, it consists of data codes, data displays, and conclusions. This study aims to find out the implementation of SPAB in educational units, especially at Quwwatul Islam Al-Qur'an Education Park (TPA) and to find out the obstacles to implementing SPAB in Quwwatul Islam Al-Qur'an Education Park (TPA). The results of the research are: the implementation of SPAB in Quwwatul Islam Al-Qur'an Education Park (TPA) is carried out for four days with SPAB facilitators.. The SPAB training produced disaster risk maps, preparedness teams, earthquake emergency programs, action plans, and evacuation routes. Obstacles to the implementation of the SPAB internalization of the 10 steps of SPAB have not been fully understood, and additional training is needed to strengthen it.